Chronic microbial infections: Manipulation of host immunity as interventional approach - Akbar, Sheikh Mohammad Fazle; Khan, Md Sakirul Islam; Mishiro, Shunji (Bangladesh Liver Journal, 2009)
Chronic viral infections represent major challenges in contemporary medicine, virology and pharmacology. The virus-bearing hosts are commonly found in every parts of the world and it is extremely difficult to manage these patients. In addition, considerable numbers of these patients develop progressive diseases and severe complications. Finally, most of these patients act as permanent reservoirs of virus. Understandings of viral life cycle during the last decade of 20th century and the first decade of 21st century have allowed development of hundreds of antiviral agents for different diseases. But, the clinical efficacy of these drugs is not yet satisfactory. In addition, virologists have provided conclusive evidences suggesting that eradication of most chronic virus from infected hosts may an unachievable goal. In this context, it is essential to develop alternative, novel, and evidence-based therapeutic maneuver for these patients. Manipulation of host immune system may be one of these approaches. We would discuss about scopes, limitations, and strategies for manipulation for controlling of chronic viral infections. The primary function of the host's immune system is to mount responses that protect the individual from various microbial infections including viruses. Host's immune responses also control the spread and virulence of the viruses [1]. This is applicable to viruses that cause acute infection. After entering the hosts, these viruses are localized in host's tissues, proliferate and induce antiviral immunity. These cellular events may cause damage and destruction of tissues and the host exhibit features of acute inflammatory diseases. However, the viruses are either almost completely eliminated from the hosts or adequately controlled in situ by host's immune systems. However, chronic infection is established by many viruses because the hosts induce improper and uncoordinated immune responses against these viruses. Most viruses cause persistent infection by evading the host immune surveillance mechanism. Both virus-related factors and host-dependent factors are primarily responsible for viral persistency in subjects with chronic viral infections. doi: 10.3329/blj.v1i1.2620 Bangladesh Liver Journal Vol.1(1) 2009 p.13-19